PENERAPAN MEDIA PEMBELAJARAN GAME EDUKATIF BERBASIS WORDWALL TERHADAP HASIL BELAJAR BAHASA INDONESIA KELAS VII G MTs NEGERI 1 BONE: PENERAPAN MEDIA PEMBELAJARAN GAME EDUKATIF BERBASIS WORDWALL TERHADAP HASIL BELAJAR BAHASA INDONESIA KELAS VII G MTs NEGERI 1 BONE - Riska; Suhardiman; Ahmad Nurul Ihsan (Jurnal Teknologi Pendidikan, 2024)
This research aims to determine the application of the wordwall game media learning model and student learning outcomes. The data collection techniques are observation, documentation, data analysis using descriptive data with frequency distribution. Based on the results of the action implementation research, it shows that the completeness score of students who completed the initial test was 7 students with a percentage of 21%. Then there were 26 students who did not complete with a percentage of 79%. The test results in cycle 1 were 11 students who completed it with a percentage of 33%, the number of students who did not complete it was 22 students with a percentage of 67%. The results in cycle 1 were still low and had not yet reached the school's KKM figure, then the test continued in cycle II with the number of students who completed it being 30 students with a percentage of 90% and 3 students who did not complete it. with a percentage of 10%. So it can be concluded that the application of the wordwall game media learning model is able to improve and enhance student learning outcomes regarding the application of the wordwall game learning media.